2003
DOI: 10.1038/sj.bjc.6601428
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of the photosensitiser Tookad® for photodynamic therapy evaluated in the Syrian golden hamster cheek pouch tumour model

Abstract: The response to photodynamic therapy (PDT) with the photosensitiser (PS) Tookad s was measured in the Syrian hamster cheek pouch model on normal mucosae and chemically induced squamous cell carcinoma. This PS is a palladium-bacteriopheophorbide presenting absorption peaks at 538 and 762 nm. The light dose, drug dose and drug injection-light irradiation times (DLI), ranging between 100 and 300 J cm À2 , 1 -5 mg kg À1 and 10 -240 min respectively, were varied and the response to PDT was analysed by staging the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 36 publications
(23 reference statements)
0
22
0
1
Order By: Relevance
“…These findings suggest the possibility of tissue selectivity or varied tissue response to the light-drug combination in VTP in the human prostate. Preclinical studies have revealed that squamous cell carcinoma and vascularized tissues have higher sensitivity to PDT with palladium-bacteriopheophorbide (17,20). Thus, the irregular boundaries seen on MR images of the prostate may be related to variations in the geometry of the blood supply or to the varied distribution of fibrotic tissue, normal tissue, and cancerous tissue in the irradiated prostate (27).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings suggest the possibility of tissue selectivity or varied tissue response to the light-drug combination in VTP in the human prostate. Preclinical studies have revealed that squamous cell carcinoma and vascularized tissues have higher sensitivity to PDT with palladium-bacteriopheophorbide (17,20). Thus, the irregular boundaries seen on MR images of the prostate may be related to variations in the geometry of the blood supply or to the varied distribution of fibrotic tissue, normal tissue, and cancerous tissue in the irradiated prostate (27).…”
Section: Discussionmentioning
confidence: 97%
“…Unlike thermal therapies, PDT with palladium-bacteriopheophorbide has been shown to offer some degree of tumor selectivity and preservation of tissue architecture (17). The primary mode of inducing necrosis with this agent has been shown to be related to the rapid induction of vascular occlusion (18)(19)(20), so this therapy might be termed vascular targeted PDT (VTP).…”
mentioning
confidence: 99%
“…These results suggest that photodynamic vascular targeting therapy needs to be improved for targeting blood vessels with high blood flow. On the other hand, because tumor blood vessels generally have slower flow rate than normal vessels (23), this finding might explain why tumor vessels are more sensitive to vascular targeting PDT than normal vessels, which has been observed in the previous study (24).…”
Section: Discussionmentioning
confidence: 82%
“…These properties include clearance from tissue within a few hours rather than within days or weeks and excitation with near infrared light, which penetrates tissue better than visible light. Examples include palladiumbacteriopheophorbide (WST09), which is excited at 763 nm and gives a strongly vascular PDT effect [13] and MV6401, which initiates a dose-dependent biphasic blood flow stasis and vascular hyperpermeability [14].…”
Section: Introductionmentioning
confidence: 99%